2023
DOI: 10.1021/acsami.3c08166
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Membrane Cloaked Cytokine Functionalized Gold Nanoparticles Create Localized Controlled Inflammation for Rapid In Vitro Wound Healing

Aqib Iqbal Dar,
Shiwani Randhawa,
Mohini Verma
et al.

Abstract: Due to impaired wound healing, millions of acute and chronic wound cases with increased morbidity have been recorded in the developed countries. The primary reason has been attributed to uncontrolled inflammation at the wound site, which makes healing impossible for years. The use of red blood cell (RBC) ghosts or erythrocyte membranes for different theranostic applications has gained significant attention in recent years due to their biocompatibility and biomimicking properties. Our study builds upon this con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…NP induced ROS generation has been reported to be one of the main cause of their cytotoxicity. 32 To find out a correlation between the observed cytotoxicity results and intracellular ROS production, we carried out a DCFDA assay with HeLa cells (Figure 3c). It was observed that Tfn@ GO APTES showed ∼62−75% of intracellular ROS production in HeLa cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…NP induced ROS generation has been reported to be one of the main cause of their cytotoxicity. 32 To find out a correlation between the observed cytotoxicity results and intracellular ROS production, we carried out a DCFDA assay with HeLa cells (Figure 3c). It was observed that Tfn@ GO APTES showed ∼62−75% of intracellular ROS production in HeLa cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%